Demographic Diversity and Economic Research: Fields of Specialization and Research on Race, Ethnicity, and Inequality - Francisca M. Antman; Kirk Doran; Xuechao Qian; Bruce A. Weinberg (Institute of Labor Economics (IZA), 2024)
Using dissertation research topics found in the EconLit database and large-scale algorithmic methods that identify author demographics based on names, we explore the link between race and ethnicity and fields of economic research. We find that underrepresented racial and ethnic minority (URM) researchers are more likely to write dissertations in some unexpected sub-fields of economics, but limited evidence that they are more likely to write dissertations on racial topics once we include basic controls. These descriptive results may be due to limitations in the data, intrinsic motivations, or external constraints.
Keywords: I23; J15; O30; 330; economic research; race and ethnicity; dissertation